Dinamika persetujuan lingkungan dalam perspektif Peraturan Pemerintah nomor 22 tahun 2021 dan peraturan turunannya - Hefni Effendi; Mursalin Mursalin; Rais Sonaji (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
Given the emergence of several new regulations in the environmental sector, stakeholders need to understand these regulations well. Therefore, this article aims to provide a practical understanding of the mechanism for compiling and evaluating environmental documents to obtain environmental approvals contained in a number of new regulations. The issuance of Government Regulation No. 22 of 2021 requires the issuance of several new Minister of Environment and Forestry Regulations. There are several new requirements that must be met in submitting an application for an environmental feasibility test, namely: Letter of direction for the preparation of environmental documents, Statement letter that the proposed activity is still in the planning stage (for new activity plans), Technical Approval, Initial approval related to the business/activity plan, Evidence of conformity of the location of the business/activity plan with the spatial plan. The authority to assess environmental documents is based on the authority to issue business permits and the establishment of a Feasibility Test Team (TUK) to replace the role of the EIA Assessment Commission (KPA).